Competency Relevance Of Graduates Of Family Education Study Program Concentration Of Tata boga With The Needs Of Work World - Resha Audia Putri; Asmar Yulastri (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This study aims to describe the Competency Relevance of Graduates of the Family Welfare Education Study Program with the Concentration of Cullinary and the needs of World Work as a whole and based on three research indicators, namely: knowledge, skills and attitudes. This type of research is a quantitative study with a descriptive approach. The population of this study were 64 alumni of the Family Welfare Education Study Program, the concentration of Cullinary, with a sample of 64 people who were taken based on the total sampling technique. Sources of data are alumni of the Cullinary Concentration Family Welfare Education Study Program in the year 2012, 2013 and 2014. The research data collection technique was carried out using a questionnaire designed based on a Likert scale that has been tested for validity and reliability. The data analysis technique was carried out by descriptive analysis and using the method of classifying the data based on the ideal score. The results of this study illustrate the Relevance of the Competence of Graduates of the Family Welfare Education Study Program with the Concentration of Cullinary as a whole who fall into the medium category. Based on the results of the study, it can be concluded that the competence of graduates of the Family Welfare Education Study Program with the concentration of tataboga is quite relevant to the competencies needed in the world of work.